Ethical Challenges in Digital Communications: Online Privacy, Security, and Responsibility - Sudi, Mohamad; Suhada, Karya; Baharudin, Muhammad Yusuf Saaih; Irwan, Irwan; Sudianto, Sudianto (Journal International Dakwah and Communication, 2024)
Social media and online communication platforms have increased significantly in today's digital era. However, these developments raise ethical challenges regarding online privacy, security and responsibility. These issues include data breaches, misuse of personal information, and the spread of inappropriate or misleading content. This research aims to identify and analyze the main ethical challenges in digital communication. Specifically, this research focuses on privacy, data security, and responsibility in sharing and using the information on the Internet. This research aims to develop a framework to address these ethical issues to increase trust and security in digital communications. This research uses a qualitative approach by collecting data through in-depth interviews and document analysis. The results of the study show that there are significant concerns regarding the handling of personal data by large and small platforms. Respondents emphasized the importance of transparency and clarity in privacy policies and the need for user education about online security. The research also identified the need for stricter ethical standards and more effective regulations to protect users. The conclusion of this research is to confirm that ethical challenges in digital communication require severe attention and coordinated action. The proposed framework includes increasing user awareness, strengthening regulations, and developing technologies that support privacy and security. Implementing these recommendations is expected to increase integrity and trust in digital communications and protect individuals' rights online.